Tumor necrosis factor alpha induces proteins that bind specifically to kappa B-like enhancer elements and regulate interleukin 2 receptor alpha-chain gene expression in primary human T lymphocytes. - Lowenthal, J W (1989)
We have investigated the biochemical basis for the activation of interleukin 2 receptor alpha-subunit (IL-2R alpha) gene expression in primary human T lymphocytes by a cytokine (tumor necrosis factor alpha), a T-cell mitogen (phorbol 12-myristate 13-acetate), and the transactivator protein (Tax) from the type I human T-cell leukemia virus. Using in vivo transfection techniques specificially designed for these primary T cells in conjunction with in vitro gel retardation and DNA footprinting assays, we found that activation of the IL-2R alpha promoter by each of these agents involves the induction of nuclear proteins that specifically interact with a kappa B-like enhancer element (i.e., an element resembling the immunoglobulin kappa-chain enhancer sequence recognized by transcription factor NF-kappa B). DNA-protein crosslinking studies revealed that primary T cells express at least three different inducible DNA-binding proteins (50-55, 70-75, and 80-90 kDa) that specifically interact with this IL-2R alpha kappa B element.